X-chromosomal STRs: Metapopulations and mutation rates - Gusmão, L.; Antão-Sousa, S.; Faustino, M.; Abovich, M. A.; Aguirre, D.; Alghafri, R.; Alves, C.; Amorim, A.; Arévalo, C.; Baldassarri, L.; Barletta-Carrillo, C.; Berardi, G.; et al. (Elsevier, 2025)
The analysis of STRs located on the X chromosome has been one of the strategies used to address complex kinship cases. Its usefulness is, however, limited by the low availability of population haplotype frequency data and lack of knowledge on the probability of mutations. Due to the large amount of data required to obtain reliable estimates, it is important to investigate the possibility of grouping data from populations with similar profiles when calculating these parameters. To better understand the partition of genetic diversity among human populations for the X-STRs most used in forensics, an analysis was carried out based on data available in the literature and new data (23,949 haplotypes in total; from these 10,445 new) obtained through collaborative exercises within the Spanish and Portuguese Working Group of the International Society for Forensic Genetics. Based on the available population data, a similarity in X-STR profiles was found in European populations, and in East Asian populations, except for some isolates. A greater complexity was found for African, South American, and South and Southeast Asian populations, preventing their grouping into large metapopulations. New segregation data on 2273 father/mother/daughter trios were also obtained, aiming for a more thorough analysis of X-STR mutation rates. After combining our data with published information on father/mother/daughter trios, no mutations were detected in 13 out of 37 loci analyzed. For the remaining loci, mutation rates varied between 2.68 × 10−4 (DXS7133) and 1.07x10−2 (DXS10135), being 5.2 times higher in the male (4.16 ×10−3) than in the female (8.01 ×10−4) germline.
Keywords: Forensic genetics; Kinship analysis; Mutation rates; Population stratification; X-STRs